Practical issues of sensor web implementation and gridification - Kussul, N.; Korbakov, M.; Kravchenko, O. (№2-3, 2008)
In this paper we provide an overview of emerging Sensor Web paradigm and show several practical issues of using Sensor Web technologies for real-world tasks. Issues under study include sensor description using SensorML and database performance for serving observations data. This paper also shows an approach for integrating standard Sensor Observation Service with Globus Toolkit Grid platform.